Symbionts commonly provide broad spectrum resistance to viruses in insects: a comparative analysis of Wolbachia strains. - Julien Martinez; Ben Longdon; Simone Bauer; Yuk-Sang Chan; Wolfgang J Miller; Kostas Bourtzis; Luis Teixeira; Francis M Jiggins (PLoS Pathogens)
In the last decade, bacterial symbionts have been shown to play an important role in protecting hosts against pathogens. Wolbachia, a widespread symbiont in arthropods, can protect Drosophila and mosquito species against viral infections. We have investigated antiviral protection in 19 Wolbachia strains originating from 16 Drosophila species after transfer into the same genotype of Drosophila simulans. We found that approximately half of the strains protected against two RNA viruses. Given that 40% of terrestrial arthropod species are estimated to harbour Wolbachia, as many as a fifth of all arthropods species may benefit from Wolbachia-mediated protection. The level of protection against two distantly related RNA viruses--DCV and FHV--was strongly genetically correlated, which suggests that there is a single mechanism of protection with broad specificity. Furthermore, Wolbachia is making flies resistant to viruses, as increases in survival can be largely explained by reductions in viral titer. Variation in the level of antiviral protection provided by different Wolbachia strains is strongly genetically correlated to the density of the bacteria strains in host tissues. We found no support for two previously proposed mechanisms of Wolbachia-mediated protection--activation of the immune system and upregulation of the methyltransferase Dnmt2. The large variation in Wolbachia's antiviral properties highlights the need to carefully select Wolbachia strains introduced into mosquito populations to prevent the transmission of arboviruses.